Dekomposisi Genetik tentang Hambatan Mahasiswa dalam Menerapkan Sifat-sifat Turunan - Wahyu Widada; Dewi Herawaty (Didaktik Matematika, 2017)
Limit was to basic concept of derivative. The results of previous research found that learners have obstacles in understanding the limit function, consequently, the occurrence of difficulties and mistakes learners understand the concept and derived principles. This study aims to determine the obstacles of learners in applying derived properties. The approach of this research is qualitative by applying task-based interview with subject of 10 students selected by certain condition from 70 students in Mathematics Education Study Program of University of Bengkulu. The researcher is the main instrument in this research which is guided by the interview sheet and duty sheet. Data analysis was performed by genetic decomposition analysis. The results of this study indicate that the barriers of learners in applying analytic concepts and properties analytically include, the tangent line almost parallel to the y-axis, the break point (cusp) at x = -4, the second derivative, the extreme point, the emergence of contradictions, asymptotes flat, and do not understand conceptually. To overcome the obstacles of learners in understanding the concept and the nature of derivatives and its application, it is suggested to apply the mathematics learning model based on the extended triad++.